Dramatic exchanges : the lives & letters of the National Theatre - Rosenthal, Daniel, 1971- (Profile Books, 2019)
There has been always as much drama offstage as on at the National Theatre, and much of it is to be found in the letters, telegrams, scribbled notes and colourful postcards of its main players. - What drove Laurence Olivier to confess: 'The foolishness of my position starts to obsess me'?- Why did Maggie Smith write: 'I am absolutely heartbroken by your decision'?- What prompted Judi Dench to ask: 'Can't you write me a musical so that I can sit on a chair in a fur hat and nothing else and sing RUDE songs?' This book brings together for the first time some of the most inspiring, dramatic and amusing letters from the life of Britain's most beloved theatre: Laurence Olivier's gracious rejection letters, Peter Hall's combative memos, Helen Mirren's impassioned defence of theatrical innovation, fantastical good luck missives and long conspiratorial letters. Together, they reveal the stories behind some of the most lavish, triumphant, daring and disastrous productions in the theatre's history, including Amadeus, Romans in Britain, Laurence Olivier's Othello, Closer, The History Boys and The Curious Incident of the Dog in the Night-Time.